PEACEKEEPING PROSPECTS OF UKRAINE AND WAYS OF LEGAL REGULATION MECHANISM IMPROVEMENT OF PARTICIPATION OF ARMED FORCES OF UKRAINE IN PEACEKEEPING OPERATIONS - Zgurovets, V.; Safoshkina, L.; Kalachova, V. (Honor and Law, 2020)
The features of the implementation of peacekeeping activities of Ukraine in the framework of the Strategy for International Peacekeeping Activities of Ukraine, approved in 15.06.2009 by № 435/2009 by the President of Ukraine, are examined and the international legal practice of participation of Ukraine in UN peacekeeping operations is analyzed. Taking into account the legal traditions, an assessment of the importance of the participation of Ukrainian Armed forces in peacekeeping operations under the auspices of the UN for Ukraine was made and recommendations were developed to improve the mechanism for legal regulation of the participation of the Armed Forces of Ukraine in peacekeeping operations. In 2009, the Decree of the President of Ukraine approved the Strategy of International Peacekeeping Activity of Ukraine, a document that outlines a prospective, strategic vision of further peacekeeping activities of the state and defines “priority goals of state participation in international peacekeeping activities, tasks and mechanisms of realization of national interests in this process”. The experience gained in peacekeeping operations abroad over the years has contributed to maintaining the combat capability of the Ukrainian military to gain experience. Ukraine earns political and image dividends by participating in peacekeeping operations, which include support for bilateral relations with coalition members and countries in the region; the opportunity to promote their military equipment and equipment in international markets and more. Today it is necessary to review the Strategy for Peacekeeping Activities of Ukraine and pay attention to the following issues: increasing the level of involvement in the System for creation and determination of the readiness of forces for participation in the UN peacekeeping and security operations; expanding the use and creation of multinational peacekeeping contingents; participation of Ukraine in EU peacekeeping operations; issues of peacekeeping training of international contingents on the territory of Ukraine. The research in the article is devoted to the issue of prospects of Ukrainian peacekeeping activities and ways of improving the mechanism of legal regulation of the participation of the Armed Forces of Ukraine in peacekeeping operations.